Offsetting the offset: Israel's strategy vis-à-vis Hamas during the 2021 Gaza War. Issue 3 (4th May 2022) - Flamer, Netanel
ABSTRACT: As the inherently weaker party in an asymmetric conflict with a state, most non-state actors tend to revert to an offsetting strategy to neutralise the adversary's advantages and exploit its vulnerabilities. To counter this strategy stronger parties might adopt a strategy defined in the article as an 'Offsetting the Offset Strategy' (OTOS). By exploring Israel's OTOS vis-à-vis Hamas during the May 2021 Gaza war, this article illustrates and analyses the nature and characteristics of this strategy. It shows that while OTOS has some significant advantages, it also entails several drawbacks that policymakers must take into account.